Submarine canyon-fill reconstruction from integrated seismic-stratigraphic analysis – application to Banquereau formation, Scotian basin – offshore Canada. - Chajin-Ortiz, Patricia; Illidge, Erick J.; Khurama, Sait (CT&F - Ciencia, Tecnología y Futuro, 2019)
Building geological models (integrating stratigraphic, structural and paleo-environmental 3D models) that allow the interpretation of sand bodies deposited by turbidity currents along submarine canyons or channels, is one of the most useful tools used by geoscientists for the definition of new drilling opportunities in both exploration and development phases. In this context, the integration of methodologies such as sequence stratigraphy and seismic attributes, together with well-log and core information, outline the basis for the interpretation of sand-body lithostratigraphy and chronostratigraphy. Similarly, these models allow the interpreter to reconstruct the depositional environment and deformation history of a sedimentary basin [1]. Based on a series of chronostratigraphic stages, this paper proposes a 3D model for the sedimentation history of the Banquereau Formation. This model is based on the integration of seismic stratigraphy, seismic attribute interpretation and well-log analysis. Also, a set of system tracts and corresponding transgression and regression phases were identified for the sedimentary interval of interest. The available dataset provided the information to identify the geometry and changes in the sedimentation patterns of the stratigraphic sequences from the Tertiary to the present, thus defining a 3D model of the sedimentological and structural architecture of this interval. Last but not least, the resulting 3D stratigraphic model made possible the identification and description of an amalgamated channel complex filling a submarine canyon associated with a fluvio-deltaic setting. This sort of analysis might be used as an analog for similar reservoirs, providing key insights and vital information for decision making.